Learning Factories The Nordic Model of Manufacturing - Holtskog, Halvor (Palgrave Studies in Democracy, Innovation, and Entrepreneurship for Growth,, 2018)
This book examines how the norms, culture, and practices of the socio-economic Nordic model give them a competitive edge in globalized production chains. Using the Norwegian automotive industry - one of the most globalized industries in the world - as the empirical foundation of the book, it examines the strengths, tensions, and challenges the Norwegian work organization style meets in this particular business environment. It explores the current indicators of competitiveness, innovation, scientific excellence, and well-being as compared with the US, UK, EU, Japan, and elsewhere to address the hotly debated question of how institutions and culture contribute to or inhibit certain forms of work organization, learning, and economic performance. Integrating action research, organization studies, and learning and innovatio n economics, this book provides a more precise understanding of how institutions and cultures at a macro level shape learning practices in a competitive industry. .